INCLUSIVE EDUCATION IN UKRAINE: SOCIAL AND PEDAGOGICAL ASPECTS - Natalia Matveeva (Vasyl Stefanyk Precarpathian National University, 2018)
The article contains the content of the term "inclusive education"; the essence of "medical" and "social" models are analyzed and defined. The author focuses on the social aspect of inclusion, highlights the importance of society in determining the place of personality in society, its socialization and further self-realization; reveals the essence of the problems that take place in practice; emphasizes ways to overcome various shortcomings and omissions in the process of social and educational inclusion. Key words: social formation, social roles, social knowledge, social stability, socialization, self-realization.